Analisis Kompleksitas Sintaksis Frasa Benda dalam Teks Naratif 'The Enchanted Fish' dan Dampaknya terhadap Keterbacaan Teks - Cahyaningrum, Dewi; Wibowo, Agus Hari (Aksara: Jurnal Bahasa dan Sastra, 2024)
This study aims to reveal the syntactic complexity of noun phrases in the narrative text "The Enchanted Fish" and its impact on the readability of the text. The research method used is content analysis with a qualitative descriptive approach. Data were taken from the text "The Enchanted Fish", an adaptation of a classic folk tale by the Brothers Grimm, and is an English teaching material for high school students in Indonesia. The analysis focused on the identification and categorization of simple and complex noun phrases in the text and how their syntactic structure affects the readability and comprehension of the text. The results showed that 63% of the noun phrases in the text were complex noun phrases, while the remaining 37% were simple noun phrases. Complex noun phrases tend to increase the difficulty level of the text, which can make it difficult for students to read and understand the contents of this narrative text. This is due to the presence of modifiers or layers of detail that explain the core part of the noun (head) in the phrase, thereby increasing the reader's cognitive load. This syntactic complexity requires students to process additional information contained in the modifiers, which often slows down reading speed and reduces overall comprehension of the text. This directly affects the readability of the text by increasing the level of difficulty and potential cognitive fatigue. These findings provide important implications for language teaching strategies, namely underlining the importance of syntactic analysis of noun phrases in order to (1) select appropriate teaching materials/texts, (2) provide structured teaching of noun phrases, and (3) provide constructive feedback in order to help students who have difficulty reading complex texts, especially in the aspect of noun phrases.Keywords: noun phrases, narrative text, text readability